The creation and implementation of the New Economic Policy: Success and failure, 1970–2008 / Che Abdul Daim Zainuddin - Che Abdul Daim , Zainuddin (2019)
The scope of this research pivots around the New Economic Policy (NEP). The research looks into several aspects namely, historical background, circumstances, other examples and the perspective of both local and international personalities concerning the necessity and formulation of the NEP. This research also looked into the conception of the Independence Documents, the accommodation of racial intolerance and the conscious decision to proceed with an unpopular mechanism to create the quota system. There were further decisions to create a middle-class tier through education and a balanced economic policy. This research throws insight into the roles of the leaders of the time in implementing the ideals of a peaceful, tolerant Malaysian society, especially with the circumstances surrounding Tun Abdul Razak, the Second Prime Minister. Any discussion regarding NEP is a constitutional matter, focusing on Article 153 which talks about the rights of all Malaysians. In this respect, the roles of the political parties and leaders of the time is discussed with regard to their hidden and open agendas, most especially the communist undercurrent concerning the loyalty of the Chinese to Malaysia. The conclusion of this research shows the success of NEP in bridging the economic gap and putting Malaysia in the path of a highly developed society in terms of education, economic and social achievement and well-being.